A Method for The Removal of Trace Iodine from Wet process Phosphoric Acid - Asadjon Qambarov; Javokhir Shamsiye; Sadoqat Abduganiyeva; Jakhongir Berdikobilov; Zarifjon Salimov; Nilufar Safarqulova (Global Scientific Publishing, 2023)
An effective method for extracting trace iodine from wet-process phosphoric acid (WPA) was designed. The iodine content in WPA was determined using an iodide-selective electrode. In addition, in this method, the sample solution, which contained approximately 2 ppm iodide, was phosphoric acid (PA) from WPA. The optimal extraction conditions were as follows: the PA/H2O2 volume ratio was 1:24, the PA/simethicone volume ratio was 1:3, the reaction time was 1 h, the reaction temperature was 45 °C, and no stirring was needed. The extraction yield of iodine reached 95%. A kinetic model was established based on bubbles with different rising velocities, and the characteristic viscosities of the gases as well as the heat flow rates of the bubbles were determined to simulate bubble movement. Then, the extraction principle was discussed, and the effect of bubble movement on extractability was analysed. The extractant (simethicone) can be recycled. Therefore, the proposed method can be considered a rapid, simple, and environmentally friendly method of extracting trace iodine from WPA
Keywords: Wet-process phosphoric acid; Extraction process of iodine; Gas bubble motion; Dynamic model